The Factors Associated with the Length of the Third Stage of Labour: A Descriptive-Analytical Study - Refaei, Mansoureh; Aghababaei, Soodabeh; Yazdkhasti, Mansoureh; Kazemi, Farideh; Farahmandpour, Fatemeh (Current Women's Health Reviews, 2022)
Background: Several risk factors have been identified for postpartum hemorrhage, one of which being the duration of the third stage of labour. This stage refers to the interval between the expulsion of the fetus to the expulsion of the placenta. Some bleeding occurs in this stage due to the separation of the placenta. Objective: This study aimed to identify the factors associated with the length of the third stage of labour. Methods: In this cross-sectional study, 300 women hospitalized for vaginal birth were selected via convenience sampling. The study data were collected using a researcher-made questionnaire. The data were then analyzed using univariate and multivariate linear regression analyses. Results: The mean (SD) age of the participants was 26.41 (6.26) years. Investigation of the relationship between the study variables and the time of placental separation indicated that a minute increase in the length of membrane ruptures caused a 0.003 minute decrease in the time of placental separation. However, this time increased by 2.75, 6.68, and 2.86 minutes in the individuals without history of abortion, those with history of stillbirth, and those who had not received hyoscine, respectively. The results of multivariate analysis indicated that suffering from preeclampsia or hypertension, history of stillbirth, not receiving hyoscine, and not receiving misoprostol increased the length of the third stage by 4.40, 8.55, 2.38, and 6.04 minutes, respectively. Conclusion: Suffering from preeclampsia and having the history of stillbirth increased and using hyoscine and misoprostol decreased the length of the third stage of labour. However, no significant relationship was found between the length of the third stage of labour and mother’s age, gestational age, parity, mother’s body mass index, mother’s chronic disorders, history of manual placenta removal, length of the first and second stages, membranes rupture, induction, amount of oxytocin after delivery, and infant’s weight and gender.
Keywords: parturition